The female athlete triad: Components, nutrition issues, and health consequences - Manore, M. M.; Kam, L. C.; Loucks, A. B. (Journal of Sports Sciences, 2007)
This paper, which was part of the International Association of Athletics Federations (IAAF) 2007 Nutritional Consensus Conference, briefly reviews the components of the female athlete triad (Triad): energy availability, menstrual status, and bone health. Each component of the Triad spans a continuum from health to disease, and female athletes can have symptoms related to each component of the Triad to different degrees. Low energy availability is the primary factor that impairs menstrual dysfunction and bone health in the Triad. We discuss nutritional issues associated with the Triad, focusing on intakes of macronutrients needed for good health, and stress fractures, the most common injury associated with the Triad. Finally, we briefly discuss screening and treatment for the Triad and the occurrence of the Triad in men.